2019
DOI: 10.1080/25726641.2019.1699361
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the reduction roasting of saprolite ores in the Caron process: microstructure evolution and phase transformations

Abstract: Fundamental studies have been undertaken to determine the microstructural and phase transformations occurring during the reduction roasting of saprolite ores. Laboratory studies have been undertaken to simulate the conditions occurring during the reduction roast step of the Caron Process. Selected serpentine samples have been treated at temperatures between 500°C and 800°C in H 2 /N 2 gas mixtures, and leaching tests on the reduced samples have been undertaken. Phase and microstructural changes have been chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(35 citation statements)
references
References 8 publications
3
32
0
Order By: Relevance
“…It has been observed previously (Chen et al 2019a) that during the reduction roasting of saprolite, the ore undergoes a series of complex transformations including dehydroxylation, reduction of NiO to Ni-Fe alloy, sintering of dehydroxylated material, and the formation and recrystallisation of olivine. Each of these processes has been found to influence the final Ni recovery from the reduced ore.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been observed previously (Chen et al 2019a) that during the reduction roasting of saprolite, the ore undergoes a series of complex transformations including dehydroxylation, reduction of NiO to Ni-Fe alloy, sintering of dehydroxylated material, and the formation and recrystallisation of olivine. Each of these processes has been found to influence the final Ni recovery from the reduced ore.…”
Section: Discussionmentioning
confidence: 99%
“…It can be clearly seen that these particles are enriched in sulfur and nickel, indicating the formation of a nickel sulfide phase. Unlike the Ni-Fe alloy observed when reduction was carried out without sulphur (Chen et al 2019a), these sulphide phases consist of predominantly nickel and sulphur with relatively little iron. Whilst no alloy particles are observed following reduction at temperatures up to 700°C, it has been found that alloy is formed at high reduction temperatures, e.g.…”
Section: Microstructural Characterisation Of Reduced Orementioning
confidence: 94%
See 2 more Smart Citations
“…At this point it is recalled that in (Chen et al 2018) it was shown, using transmission electron microscopy (TEM), that after direct reduction of the ore at 800°C…”
Section: Effect Of Sinteringmentioning
confidence: 99%